Spectrum women : walking to the beat of autism - Cook, Barb; Garnett, Michelle; Artemisia, Rudy; Stewart, Catriona; Lesko, Anita; Willey, Liane Holliday; Craft, Samantha; Purkis, Jeanette; Ross, Kate (Jessica Kingsley Publishers, 2018)
"Barb Cook and 15 other autistic women describe life from a female autistic perspective, and present empowering, helpful and supportive insights from their personal experience for fellow autistic women. Michelle Garnett's comments validate and expand the experiences described from a clinician's perspective, and provide extensive recommendations. Well-known writers including Liane Holliday Willey, Anita Lesko and Kate Ross offer their personal guidance on significant issues that particularly affect women, as well as those that are more general to autism. Contributors cover growing up, identity, diversity, parenting, independence and self-care amongst many others. With great contributions from exceptional women, this is a truly well-rounded collection of knowledge and sage advice for any woman with autism." --Publisher description.